2017
DOI: 10.1182/bloodadvances.2017007898
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing for RH genotyping and alloimmunization risk in children with sickle cell anemia

Abstract: Key Points• WES can be applied for precise RH genotyping, detection of new or uncommon variants, and determination of RHD zygosity.• An altered RH genotype is a risk factor for Rh alloimmunization in patients with sickle cell anemia.RH genes are highly polymorphic and encode the most complex of the 35 human blood group systems. This genetic diversity contributes to Rh alloimmunization in patients with sickle cell anemia (SCA) and is not avoided by serologic Rh-matched red cell transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 22 publications
3
77
1
Order By: Relevance
“…Several studies have reported allele prevalences for other populations [18,19,44,45,46]. Partial RH2 antigens appear to be particularly prevalent in mainland France, whereas partial RH1 antigens are more prevalent in Guadeloupe and French Guiana.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported allele prevalences for other populations [18,19,44,45,46]. Partial RH2 antigens appear to be particularly prevalent in mainland France, whereas partial RH1 antigens are more prevalent in Guadeloupe and French Guiana.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of partial RH antigens and variant RH alleles in SCD patients has recently been investigated in France [11,17] and elsewhere [15,18,19]. SCD patients with variant alleles have been shown to have a higher risk of alloimmunization, in both these and other studies [20].…”
Section: Part I: Overview and Presentation Of The French Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of successful clinical applications have been reported, and further efforts are under way in the areas of oncology, hemostasis, obstetrics, and pharmacology to identify the clinical benefits of genomic medicine . Transfusion medicine is an additional discipline with a strong genetics foundation that is exploring this approach …”
mentioning
confidence: 99%
“…Next-generation or massive parallel sequencing have proven the principle for blood group determination in such patients, but are still under further development and therefore not addressed within this issue [5,6,7]. Based on their everyday experiences, however, Castilho and Dinardo [8] are reporting on the ‘Brazilian Way', and Floch et al [9] on the ‘French Strategy' to support SCD patients by best matching strategies and the meaning of blood group genotyping in this context.…”
mentioning
confidence: 99%